2019
DOI: 10.1051/e3sconf/201913603018
|View full text |Cite
|
Sign up to set email alerts
|

Thermal design optimization and analysis on heating load of rural buildings in northern China

Abstract: The envelope of rural buildings has been lack of effective and reasonable thermal insulation method and therefore its energy consumption has always been high. In order to address this problem, this paper aims to optimize the thermal design of building envelope. The simulation using DesignBuilder software for modeling and analyzing, using the orthogonal experimental design method to study the effects of external wall, external window and roof on heating load, and optimal thermal insulation scheme was obtained, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Few studies investigate rural building envelope energy efficiency. A few case studies calculate the energy-saving potential, costs, and benefits of building energy retrofits in China (see Table S2 for a relevant literature review). For example, Cui et al found that retrofitting a typical rural house in Shandong to meet the current design standard can lead to a ∼70% efficiency improvement, yet they did not estimate the cost of such a retrofit nor did they evaluate the resulting change in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies investigate rural building envelope energy efficiency. A few case studies calculate the energy-saving potential, costs, and benefits of building energy retrofits in China (see Table S2 for a relevant literature review). For example, Cui et al found that retrofitting a typical rural house in Shandong to meet the current design standard can lead to a ∼70% efficiency improvement, yet they did not estimate the cost of such a retrofit nor did they evaluate the resulting change in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%